Uncommon Multicystic Lesion of the Interventricular Septum in a 7-Year-Old Boy: Unusual Presentation of an Intracardiac Teratoma - Kahlbau, H (2016)
Intracardiac teratomas are very rare primary cardiac tumors; only a few cases have been reported. We present the case of a 7-year-old boy who early in life showed pulmonary stenosis and needed percutaneous and surgical procedures, including sectioning of the right ventricular bands and reconstruction of the right ventricular outflow tract. At the age of 7 years the patient received a diagnosis of a multilobular cystic mass in the right ventricle adherent to the interventricular septum, which was not present at birth. Successful surgical resection was performed. Histologic examination revealed a mature teratoma. We emphasize the differential diagnosis of teratomas in cystic lesions of the interventricular septum.